Tsallis Entropy-Regularized Fuzzy Classification Maximum Likelihood Clustering with a t-Distribution - Suzuki, Yuta; Kanzawa, Yuchi (Journal of Advanced Computational Intelligence and Intelligent Informatics, 2025)
This study proposes a fuzzy clustering algorithm based on fuzzy classification maximum likelihood, t-distribution, and Tsallis entropy regularization. The proposed algorithm is shown to be a generalization of the two conventional algorithms, not only in the use of their objective functions, but also at their algorithmic level. The robustness of the proposed algorithm to outliers was confirmed in numerical experiments using an artificial dataset. In addition, experiments using 11 real datasets demonstrated the superiority of proposed algorithm in terms of the clustering accuracy.